PERLINDUNGAN HUKUM BAGI KREDITUR TERHADAP PERJANJIAN KREDIT KONSTRUKSI - Nur Fatimah Azzahra; Syamsuddin Baco; Zulkarnain Zulkarnain (Universitas Tadulako, 2025)
This development requires financing in the form of construction loans, which are usually facilitated by financial institutions or banks for the implementation of the construction project. The existing regulations in Indonesia must be obeyed and implemented properly, especially for law enforcers, so as to provide legal protection for the community. Therefore, the need for legal protection makes it easy to face a problem related to the law. The creditor agreement process, be it construction credit, is always followed by an agreement and additional guarantees as protection for the bank that the debtor will carry out its achievements according to the agreement. In this study, it is a form of legal protection for creditors that can be provided to creditors in construction credit agreements. The credit given to the debtor is, of course, additional collateral given to the creditor, but the debtor's payment is not sufficient for credit payments, especially construction credit agreements. Construction credit agreements have the peculiarity of involving the object in the form of the implementation of construction projects whose development is long-term and gradual. The cause of the implementation of the construction project is hampered by natural factors and human factors. In addition, creditors' efforts to resolve disputes in construction credit agreements, where it is common for debtors to not agree to the settlement efforts given by creditors, defaults, non-tax collateral values, project delays, etc. The research methodology uses the normative legal research method. The source of the research approach is the legislative approach and the concept approach with primary, secondary, and tertiary sources of legal materials. The results of this study are that legal protection for creditors can be strengthened through creditors paying attention to the terms of credit, the position of additional guarantees, and the need for clearer regulations and legal certainty related to legal protection for creditors in credit agreements between creditors and debtors. In the creditor's efforts to resolve disputes in construction credit agreements, that can be carried out such as by means of negotiation aimed at preventing disputes from developing further and avoiding greater losses for both parties in the settlement of the credit agreement so that civil lawsuits are not filed in the District Court. The results of this research can provide input for the improvement of laws and regulations in the banking world, protection for creditors, and efforts to resolve banking disputes.